2013
DOI: 10.1371/journal.pone.0080508
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the Complete Chloroplast Genome into the Evolution of Sesamum indicum L

Abstract: Sesame (Sesamum indicum L.) is one of the oldest oilseed crops. In order to investigate the evolutionary characters according to the Sesame Genome Project, apart from sequencing its nuclear genome, we sequenced the complete chloroplast genome of S. indicum cv. Yuzhi 11 (white seeded) using Illumina and 454 sequencing. Comparisons of chloroplast genomes between S. indicum and the 18 other higher plants were then analyzed. The chloroplast genome of cv. Yuzhi 11 contains 153,338 bp and a total of 114 unique genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 56 publications
8
65
0
Order By: Relevance
“…M. multicaulis contained 22 genes (eight tRNA, 12 PCGs, and two pseudogenes), with one intron, which is consistent with that found for M. atropurpurea, with the exception of two genes (ycf3 and clpP) that contain two introns (Table 2). Of the 22 genes, 10 are situated within the IR region (4 PCGs, 4 tRNAs, and 2 pseudogenes), 1 in the SSC region (ndhA), and 11 in the LSC region (7 PCGs and 4 tRNAs), and this study also found trnK-UUU has the largest intron that contains the protein-coding gene matK, which is similar to that found in green plants (Zhang et al, 2013).…”
Section: Genome Content and Organizationsupporting
confidence: 80%
See 3 more Smart Citations
“…M. multicaulis contained 22 genes (eight tRNA, 12 PCGs, and two pseudogenes), with one intron, which is consistent with that found for M. atropurpurea, with the exception of two genes (ycf3 and clpP) that contain two introns (Table 2). Of the 22 genes, 10 are situated within the IR region (4 PCGs, 4 tRNAs, and 2 pseudogenes), 1 in the SSC region (ndhA), and 11 in the LSC region (7 PCGs and 4 tRNAs), and this study also found trnK-UUU has the largest intron that contains the protein-coding gene matK, which is similar to that found in green plants (Zhang et al, 2013).…”
Section: Genome Content and Organizationsupporting
confidence: 80%
“…It is believed that the locations of SSC/IR and LSC/IR junctions are markers of chloroplast genome evolution (Zhang et al, 2013). Here, we compared the positions of the IR/SC boundary in six complete cpDNA sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chloroplast genomes of the Hawaiian mints demonstrate the typical angiosperm quadripartite structure, and the gene content, order, and GC content were consistent with most other members of the Lamiales (Mariotti et al, 2010;Wicke et al, 2014;Zhang et al, 2013). The Hawaiian mint genome did not demonstrate any rearrangements or inversions, which have been found in Jasmin nudiflorum, Schwalbea americana, and a few other species (Welch et al, 2016) (Lee et al, 2007;Wicke et al, 2013).…”
Section: Mint Chloroplast Genome Structure and Variabilitymentioning
confidence: 51%